PT Matahari Department Store TBK Income Statement Analysis - Putra, Fachrul Ananda; Pangestu, Rizcki (iora, 2024)
This research aims to find out how each income variable contributes to total income and analysis of financial performance at PT Matahari Department Store Tbk (Matahari), which is one of the leading retail companies in Indonesia that provides clothing, accessories, beauty and household products using the ratio financial Return On Investment (ROI), Net Profit Margin (NPM), Total Asset Turnover (TATO) from 2019 to 2023, then financial performance using the Du Pont approach analysis. This research uses a qualitative descriptive research method. And from the research results we can show that the condition of the profit and loss report at PT Matahari can be said to be quite good even though there are fluctuations in the contribution of income and total income variables and are in a negative condition. With the du pont system analysis, financial performance has increased even though it is still in a negative condition too. This is influenced by the percentage of net profit or NPM which experiences a negative decrease in losses and is followed by an increase in the TATO value.